2018
DOI: 10.21475/ajcs.18.12.11.p1283
|View full text |Cite
|
Sign up to set email alerts
|

Performance of tomato rootstocks in False Root-knot Nematode (Nacobbus aberrans) infested soil

Abstract: Nacobbus aberrans, known as the "false root-knot nematode", has drawn special attention since it affects large areas of tomato production in Latin America. The aim of this study was to evaluate two rootstocks, Solanum lycopersicon L. var. cerasiforme 'Carolina' and S. lycopersicon L. 'Maxifort', onto which S. lycopersicon L. 'Santa Clara' was grafted. In addition to these, non-grafted 'Santa Clara' plants were used as control. Grafting was carried out 30 days after sowing, both for scion and for rootstocks. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…In this work, both proline and total and reducing sugars contents were higher in plants inoculated with N. aberrans in contrast to the controls without nematode. This coincides with the nding of Garita et al (2018), who observed that grafted and ungrafted tomato plants, in the presence of Nacobbus aberrans, presented higher proline content. Similar results were obtained by Mahapatra and Nayak (2019) in pumpkin, where the plants inoculated with Meloidogyne incognita had a greater accumulation of proline and total sugars in shoots and roots.…”
Section: Resultssupporting
confidence: 90%
“…In this work, both proline and total and reducing sugars contents were higher in plants inoculated with N. aberrans in contrast to the controls without nematode. This coincides with the nding of Garita et al (2018), who observed that grafted and ungrafted tomato plants, in the presence of Nacobbus aberrans, presented higher proline content. Similar results were obtained by Mahapatra and Nayak (2019) in pumpkin, where the plants inoculated with Meloidogyne incognita had a greater accumulation of proline and total sugars in shoots and roots.…”
Section: Resultssupporting
confidence: 90%
“…Disease-resistant or disease-tolerant rootstocks (Fullana et al, 2023;Rabelo et al, 2018), important in integrated management, can reduce production costs and are agroecologically correct (Ito et al, 2014). Tomato grafting, on domesticated or wild cultivars or plant species (Farias et al, 2013), can improve disease and pest management (Garita et al, 2018(Garita et al, , 2019Sabatino et al, 2013) without causing environmental impacts compared to other traditional control methods (Doñas-Uclés et al, 2014), in addition to improving product quality (Loos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Una de éstas es el uso de portainjertos, con los cuales se busca conferir sistemas radicales abundantes, que permiten una mayor absorción de agua y nutrimentos que, de manera consecuente, mejoren el rendimiento. Es importante estudiar el vigor potencial en el desarrollo de estos materiales, ya que se han registrado casos de injertos en los cuales las respuestas han sido contrarias a lo deseable; es decir, hubo reducción en el crecimiento apical y en la biomasa seca de las púas (Garita et al, 2018); en otros casos, algunas combinaciones afectaron negativamente el rendimiento (Kacjan Maršić y Osvald, 2004) y caracteres de fruto como contenido de ácido ascórbico, acidez titulable, contenido de sólidos solubles, fenoles totales y actividad antioxidante (Vrcek et al, 2011).…”
Section: Introductionunclassified